Use of Acute Psychiatric Hospitalisation: A Study of the Factors Influencing Decisions to Arrange Acute Admission to Inpatient Mental Health Facilities - Nathan, Rajan; Gabbay, Mark; Boyle, Sean; Elliott, Phil; Giebel, Clarissa; O'Loughlin, Carl; Wilson, Pete; Saini, Pooja (Frontiers in Psychiatry, 2021)
Background: Human decision-making involves a complex interplay of intra- and inter-personal factors. The decisions clinicians make in practice are subject to a wide range of influences. Admission to a psychiatric hospital is a major clinical intervention, but the decision-making processes about admissions remain unclear. Aims: To delineate the range of factors influencing clinicians’ decisions to arrange acute psychiatric admissions. Methods: We undertook six focus groups with teams centrally involved in decisions to admit patients to hospital (crisis resolution home treatment teams, liaison psychiatry, approved mental health practitioners and consultant psychiatrists). The data were analysed using qualitative thematic analysis. Results: Our data show a complex range of factors influencing decision making that were categorised as those related to: (i) Clinical or Risk factors; (ii) Threat or fear factors influencing Clinicians; (iii) Interpersonal dynamics between staff and patients; (iv) Contextual factors. Conclusions: Decisions to arrange acute admission to hospital are not just a result of the appraisal of clinical and risk-related information. Emotional, interpersonal and contextual factors are also critical in decision-making. Delineating the breadth of factors that bear on clinical decision-making can inform approaches to (i) clinical-decision-making research, (ii) the training and supervision of clinicians, and (iii) service delivery models.